Prevalence of coronary artery disease in young sudden death cases and correlation with post-mortem computed tomography calcium score / Omar E. … [et al.] - Omar, Effat; R., Faizuddin; Chaincel Singh, Mansharan Kaur; Rahimi, Razuin; Mahmood, Mohd Shah; Abdullah, Nurliza; Abdul Manaf, Zaleha; Nawawi, Hapizah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Data on prevalence of coronary atherosclerosis and coronary artery disease (CAD) in young sudden death autopsy cases in Malaysia are still scarce. Calcium scoring (CS) on Computed Tomography (CT) was suggested to be predictive for CAD; however the reports have been conflicting. Objectives: to investigate (i) the prevalence of young CAD in sudden death cases in a Malaysian population; (ii) the association between CT CS and CAD in such cases and correlation with age. Methods: Sudden death cases received at the National Institute of Forensic Medicine, Kuala Lumpur between September 2012 and December 2013 were recruited. The cases were divided into young [=40] and old [>40 years old] age groups. Presence of CAD was recorded during autopsy. Results: A total of 155 cases was included; 64.5% of the subjects were below 40 years old. CAD was the cause of death of 34 [21.9%] cases; of these, young individuals comprise 47.1% of cases [n=16; 10.3% of total cases, 16% of young sudden death cases]. Both young and old subjects with CAD had lower CS compared to those without CAD [p<0.000; p=0.003 respectively]. Multivariable regression analysis showed CS to be significantly correlated with CAD in both young and old subjects. In contrast, other factors such as gender, ethnicity, body-mass index and waist-hip ratio did not show any correlation with CAD in both groups. Conclusion: The revalence of CAD in young sudden death cases is relatively high. CS is useful in discriminating CAD in both young and old SD subjects.